Serum Levels of Interleukin-10 as a Potential Indicator of Outcome in Premature Neonates with Respiratory Distress Syndrome - Seyedeh Zohreh Jalali; Fatemeh Yousefi; ّFarshid Saadat (Iranian Journal of Neonatology, 2022)
Background: Respiratory distress syndrome (RDS) is one of the major causes of mortality in preterm newborns. Regarding the close association between inflammatory pathways and the occurrence of RDS, the present study aimed to determine the serum level of interleukin-10 (IL-10) in premature neonates with and without RDS. Methods: In this case-control study, the serum level of IL-10 was assessed by immunoassay method in both groups of 30 premature neonates with RDS and 28 newborns without RDS as controls. Statistical analysis was conducted to compare potential variations among premature neonates with or without RDS. Results: The mean level of IL-10 was significantly higher in neonates with RDS, compared to the non-RDS group (41.20±75.78 pg/ml versus 7.73±14.31 pg/ml, P=0.014, respectively). The IL-10 was significantly higher in non-survived neonates, compared to survived newborns (178.76±69.67 pg/ml vs. 6.81±4.06 pg/ml, P=0.0001). In multivariate linear regression analysis, the presence of RDS was associated with the increased level of serum IL-10 (Beta=1.038, P=0.001). Conclusion: This study revealed that the increased serum levels of IL-10 in premature neonates with RDS might be considered an early indicator of fatal outcomes with high specificity.